Charakterystyka nakopalnianej pracowni krzemieniarskiej z okresu schyłkowego paleolitu na podstawie materiałów krzemiennych ze stanowiska Kłodawa 3, pow. gorzowski, woj. lubuskie - Rakoca, Aleksandra; Rozbiegalski, Piotr (Folia Praehistorica Posnaniensia, 2015)
Discoveries of mine-type workshop linked to hunter-gatherers within the Polish Plain have been rare. In 2001, excavations at site 3 in Kłodawa, Gorzów county, ended providing a rich collection of flint artefacts. Technological and typological analysis permitted interpretation of the collected assemblages as remnants of a Final Palaeolithic mine type workshop related to the Swiderian-Ahrensburgian technocomplex.